Transformation of Football in Papua within the Framework of Social Integration, Conflict, and Peace - Fredrik Sokoy; Rif'iy Qomarrullah; Heppy Hein Wainggai (Journal of Physical Education Health and Sport, 2025)
Soccer in Papua is more than just a set of physical activities; it serves as a social and cultural platform that brings together various issues regarding conflict, identity, and community cohesion. This study explores the role of soccer in Papua, particularly in relation to issues of conflict, peace, and social unity. The main focus of this study is to show how this sport impacts interactions within communities and contributes to the process of local conflict resolution. Using a qualitative approach that includes document analysis, semi-structured interviews, and participatory observation in a number of communities, this study analyzes the experiences of players, community leaders, fans, and organizers involved in inter-village and inter-district competitions. The findings show that soccer acts as a tool for cultural diplomacy within communities, easing tensions between competing groups, encouraging cooperation, and strengthening collective identities that transcend ethnic and geographical boundaries. However, challenges remain regarding security management, unequal access to facilities, and a lack of regulations that support sports programs for peace. This research adds to the growing body of knowledge on sports and peacebuilding by presenting new evidence from Papua, where soccer not only strengthens community bonds but also fosters.